О регулярности обобщенных решений третьей краевой задачи для эллиптического дифференциально-разностного уравнения - Цветков, Е.Л. (Український математичний журнал, 1995)
Unlike the case of elliptic differential equations, generalized solutions of elliptic difference-differential equations may be not smooth in a domainQ but remain smooth only in certain subdomainsQ r ⊂Q Conditions are considered which are necessary and sufficient for generalized solutions of the third boundary-value problem to preserve smoothness on the boundary of adjacent subdomainsQ r .